Shortest These search Heading Attractions Lubukpakam Using Greedy Algorithm - SITORUS, IRMA YOLANDA; HASUGIAN, PENDA SUDARTO (Journal of Computer Networks, Architecture and High Performance Computing, 2020)
In the case of this shortest route search actually has many different types of solutions for path searching, for example the greedy algorithm, dijkstra, floyd-warshall and bellman-ford but what is commonly used to solve this problem is the Greedy algorithm because this algorithm is an algorithm that uses a problem solving approach with look for a temporary maximum value at each step. Of all the tourist attractions such as the Fruit Garden, Deli Serdang Swimming Pool, Deli Serdang Museum, Deli Serdang Regency Government Square, Tengku Raja Muda Field, the writer will look for the shortest path to take the closest route because of the many paths that can be taken to get the optimum path as well as using google maps. This application is made web-based with PHP and MySQL scripts as a database manager so that it is enough to connect to the internet network that everyone can easily access.